Pengaruh Kinerja Keuangan terhadap Price Book Value disaat Pandemi Covid-19 pada Bank Umum di Indonesia - Achmad Zaki (Universitas Islam Kadiri, 2023)
At the beginning of 2020 economic development in Indonesia experienced a slowdown due to the Covid-19 pandemic which had an unfavorable impact on service and goods companies, namely by limiting operational performance which greatly affected the decrease in income earned, especially service companies such as bank companies. The purpose of this study was to examine the condition of the capital adequacy ratio, return on assets, and net interest margin at banks in Indonesia during the Covid-19 pandemic. The research sample consists of fifteen banks, which use a saturated sampling approach, namely banks listed on the Indonesian stock exchange and the data used is secondary data obtained from annual reports and the Indonesia Capital Market Directory (ICMD) on audited banks from 2020 until 2021 which can be accessed on the IDX website. This study uses multiple regression analysis to test three financial ratios, namely capital adequacy ratio (CAR), return on assets (ROA), and net interest margin (NIM) to Price Book Value (PBV). The findings of this study reveal that the capital adequacy ratio (CAR), return on assets (ROA), and net interest margin (NIM) have a significant positive effect on Price Book Value (PBV) during the COVID-19 pandemic